The development of a three tier diagnostic test to identify misconception on food chain feeding relationships - Kurnia Fadila; Nahadi Nahadi; Taufik Rahman (JURNAL BIOEDUKATIKA, 2021)
This study was aimed to develop a Three-Tier Diagnostic Test instrument to identify students' alternative conceptions about Food Chain Feeding Relationships. This instrument was developed based on stages of development proposed by Treagust. This study involved 102 students of grade VII. There were 4 students included in the interview, 28 students answered the open-ended questions, and 70 students were involved in the implementation of instrument developed. The instrument items' content was then validated by five expert judgment. The analysis showed that the Content Validity Ratio and Content Validity Index value for nine items was 1, while an item acquired 0.6 value. This indicated that Food Chain Feeding Relationships Diagnostic Instrument (FCFRDI) is valid and feasible to be tested on students. The test result data were analyzed using the Rasch Model to determine the item fit and reliability. The difference between item reliability value and the person reliability demonstrated a significant result, which means that the instrument developed has good item quality. Overall, it can be concluded that the FCFRDI developed has met the content and empirical validity so that it can be used to identify students misconceptions.